2015
DOI: 10.4172/1204-5357.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Transportation Algorithm for Selecting Bank Merger Partners

Abstract: JIBC August 2015, Vol. 20, No.2 -2 -After the experience of the 1997 Asian Financial Crisis, the Malaysian government initiated the consolidation of the commercial banking sector with the aim of creating a core group of strong and well capitalized banking institutions. The first phase of the consolidation was completed by the end of 2001. As a result, the number of domestic banks in the commercial banking sector was reduced from a total of twenty to ten anchor banks which were in compliance with minimum capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Thus, the paper also tried to evaluate the performance of the Nepalese commercial banks using the EAGLES Model developed by Dang and Vong (2020). Balachandher et al (2015) found that an evaluation of the Malaysian banks' performance parameters under the EAGLES model will give a proper insight into the banks' financial status in the due process of the initial stage of the merger process. The study found that the rating of the banks using the EAGLES model would give proper information at an initial stage for selecting a suitable partner for the banks which are eager to go for a merger or acquisition process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the paper also tried to evaluate the performance of the Nepalese commercial banks using the EAGLES Model developed by Dang and Vong (2020). Balachandher et al (2015) found that an evaluation of the Malaysian banks' performance parameters under the EAGLES model will give a proper insight into the banks' financial status in the due process of the initial stage of the merger process. The study found that the rating of the banks using the EAGLES model would give proper information at an initial stage for selecting a suitable partner for the banks which are eager to go for a merger or acquisition process.…”
Section: Introductionmentioning
confidence: 99%